Experience with tocilizumab in patients with rheumatoid arthritis (according to the data of the LORNET multicenter trial) - E Yu Panasyuk; V N Amirdzhanova; Anastasia Sergeyevna Avdeyeva; E L Luchikhina; E N Aleksandrova; A A Novikov; E L Nasonov (Научно-практическая ревматология)
Objective: to estimate quality of life changes in patients with rheumatoid arthritis (RA) while adding tocilizumab (TCZ) to therapy with disease-modifying antirheumatic drugs (DMARDs) and to study the efficiency and safety of the therapy in RA patients with an inadequate response to previous DMARD treatment. Subjects and methods. 201 patients with RA were examined. All the patients received six intravenous infusions of TCZ 8 mg/kg at a 4-week interval during stable therapy with DMARDs and glucocorticoids. The EULAR/ACR classification criteria and SDAI and CDAI were used to evaluate the efficiency of TCZ therapy. Remission was assessed by the EULAR criteria. Results and discussion. Prior to TCZ therapy, median [25th to 75th percentiles] DAS28 6.8 [6.1 to 7.4], SDAI 41.8 [34.6 to 53.7], and CDAI 39.2 [31.4 to 49.5] corresponded to high RA activity. At week 4 of TCZ therapy, there was a reduction in DAS28 (4.6 [3.8 to 5.4]), SDAI (24.6 [17.8 to 33.4]), and CDAI (23.6 [17.5 to 32.0]), which was retained until 24 weeks (р < 0.01). At week 24 of TCZ therapy, good and fair effects according to the EULAR criteria were observed in 133 (70.4%) and 54 (28.6%) patients, respectively; no effect was seen in 2 (1.1%) patients. The ACR20/50/70 effect was recorded in 89.1, 70.6, and 44.3% of the patients, respectively. EULAR and SDAI remissions were achieved in 51.3 and 21.4%, respectively. There were improvements in functional status and quality of life according to the EQ-5D and SF-36 questionnaires. C-reactive protein levels and erythrocyte sedimentation rate normalized 4 weeks after the first infusion of the drug and remained until week 24 of treatment. Conclusion. Thus, an analysis of the data of the Russian trial convincingly suggests that TCZ is effective and well tolerated in severe RA resistant to standard therapy with DMARDs.